Психологічні аспекти професійної діяльності суддів апеляційного суду - Балабанова, Л. М.; Коваль, А. А.; Balabanova, L. M.; Koval, A. A. (Право і безпека. - 2016. - № 1 (60). - С. 146–151, 2016)
Актуальність дослідження діяльності суддів з точки зору психології спрямована на вирішення одного з найважливіших завдань судової системи – розроблення шляхів оптимізації професійної діяльності та особистісного розвитку суддів, особливо в період кардинального реформування судової системи. В результаті проведеного дослідження встановлено, що судовий розгляд являє собою складну психологічну картину, припускає серйозне напруження мислення, спостережливості. Підвищена навіюваність або самонавіювання, яскраво виражений суб’єктивний тип установки дуже ускладнюють роботу судді та можуть спричинити низку дефектів.

This article is devoted to studying the psychological aspects of professional activities of the judges. The objective of the study is to identify the characteristics of judges’ personality working in the court of appeal. Psychological features of professional activities of judges concern psychological patterns of legal enforcement activities, studies of the psychological basis of a judge’s job description, individual style and skills, development of professional skills, selection and placement of personnel, vocational guidance, professional selection, professional training and formation of the personality of a judge. As a result of the conducted study it is found out that the trial is a complex psychological picture involves serious stress of thinking, observation. Increased suggestibility or self-hypnosis, a distinct subjective type of installation seriously complicate the work of judges and can cause a number of defects. Studying the shadow sides of life, sometimes in the most vulnerable manifestations, a judge must be able to maintain personal immunity of negative effects and avoid unwanted distortion of personality, the so-called professional deformation, which can be manifested into the transformation of vigilance into excess suspicion, fault-finding, distrust of any person. In this regard it is necessary to have not only professionally important qualities, but such psychological knowledge and skills that would ensure resilience to the negative impacts of these factors and contributed to realization of professional activity at a high level without compromising health. The future judicial reform in Ukraine should also concern this field – it is necessary to create the most favorable working conditions for judges, to implement psychological support of judicial activities to achieve the maximum effectiveness of their work.

Актуальность исследования деятельности судей с точки зрения психологии направлена на решение одной из важнейших задач судебной системы – разработки путей оптимизации профессиональной деятельности и личностного развития судей, особенно в период кардинального реформирования судебной системы. В результате проведённого исследования установлено, что правосудие представляет собой сложную психологическую картину, предполагает серьезное напряжение мышления, наблюдательности. Повышенная внушаемость или самовнушение, ярко выраженный субъективный тип установки очень усложняют работу судьи и могут вызвать ряд дефектов.
Psychological aspects of professional activity of judges of the court of appeal
Психологические аспекты профессиональной деятельности судей апелляционного суда
Балабанова, Л. М. Психологічні аспекти професійної діяльності суддів апеляційного суду / Л. М. Балабанова, А. А. Коваль // Право і безпека. - 2016. - № 1 (60). - С. 146–151.
Balabanova, L.M. and Koval, A.A. (2016), “Psychological aspects of professional activity of judges of the court of appeal” [“Psykholohichni aspekty profesiinoi diialnosti suddiv apeliatsiinoho sudu”], Pravo i Bezpeka, No. 1, pp. 146–151.
Keywords: Психологія. Рsychology. Психология; юридична психологія; юридическая психология; суддя; особистість; мислення; поведінка; психологічне супроводження; judges; personality; thinking; behavior; psychological support; судья; личность; мышление; поведение; психологическое сопровождение